Let's talk about staying in a shelter - Weitzman, Elizabeth (New York Rosen Pub. Group's PowerKids Press, 1996)
Briefly describes various kinds of shelters for people without permanent homes and discusses how to deal with living in one.
Includes index.
660
660
Accelerated Reader AR
Keywords: Shelters for the homeless -- United States -- Juvenile literature; Homeless children -- United States -- Juvenile literature